ENHANCE DESIGN INDUSTRIAL REVOLUTION DEVELOPMENT TECHNIQUE 4.0 EVEN COVID 19 - Solly Aryza (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
The development of technology that can be felt and implemented distance education in Indonesia directly is one of the Integrated Indonesian Open and Open Online Education (PDITT) programs that have been reserved by the Directorate General of Higher Education. This research intended to discuss and analyze the implementation of online learning (distance learning) in engineering science held by Aircraft Politechnic. This research was carried out based on several e-learning lecture activities in each subject taught. Various strategies both at the planning, implementation, and problem-solving stages are presented in this paper to be used as a reference for future online learning programs in engineering science.